A death in Vienna - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2005)
Hero Gabriel Allon is a restorer of paintings and frescoes and also a reluctant member of Israeli intelligence. Action and suspense abound in this serious fiction with a serious purpose.